Сексуальное образование — глобальная задача XXI века - Кон, И. (Социология: теория, методы, маркетинг, 2009)
The sexual revolution of the XXth century, by drastically changing sexual culture and practices, had made absolutely necessary special programs of sexuality education for children and youth. Scientific knowledge about human sexualities is a precondition of sexual and reproductive health Access to sexual information is one of the basic human rights. Liberalization of sexual morality without an appropriate information about the involved sexual risks inevitably produces an increase of unwanted pregnancies, abortions, STDs and HIV. WHO, UNAIDS and other international organizations unanimously consider sexua - lity education as a global issue of the XXIst century. However, the introduction of such programs is related with serious social and educational difficulties. That’s why it has strong ideological opposition. The article compares two main rival world strategies – US strategy of complete sexual abstinence until marriage and European models of comprehensive sexuality education – and comes to the conclusion that, according to reliable social and medical statistics, alternative European strategies are much more effective and realistic. The necessity of close cooperation between medical sexologists, social scientists and educators is emphasized.